Elucidation of Relationship between Phytophthora Leaf Blight and Fruit Rot in Tomato - Ghatak, Abhijeet; Ansar, Mohammad; Ghatak, Lajja Vati; Balodi, Rekha (Journal of Postharvest Technology, 2015)
Field experiments were carried out in order to determine the efficacy of  traditional and new fungicides for preharvest and postharvest management to  late blight disease of tomato. Preharvest management was followed by  application of traditional fungicide and combination of fungicides. The  combination of Mancozeb with Cymoxanil and Mancozeb with Phenamidone  rendered fruit rot incidence between 8.0% and 9.3%, indicating most effective  fungicides to manage this disease. Similarly, evaluation of type cultivar  (determinate/indeterminate) response was done in the field. This results the  intimate relation between infection in leaf and infection in fruit for the  determinate cultivars (R2= 0.96). The experiments under high field epidemics (65.0% and 96.5% on leaves and fruits, respectively) have generated  preliminary information on relationship between late blight severity on leaves  and fruit rot incidence. Our study reveals late blight epidemics both on leaves  and on fruits accelerated from the third week of February, which suggests  special attention should be taken during this period. The laboratory  experiments considered assessment of isolates of Phytophthora, and  identification of most virulent isolate of the late blight fungus. Evaluation of  infection and its progress on fruits, collected from fungicide treated plots and  water sprayed plots, was made. Infection on fruits sampled from the plots  treated with previously mentioned combination of fungicides had not  progressed significantly (P < 0.05) compared with the fruits collected from  plots treated with other fungicides. Occurrence of percent infection was  estimated under laboratory in collections of fresh fruit (artificially inoculated)  treated with fungicides. Similar result, as exhibited in the field experiments and experiment on infection progress, was obtained from the postharvest  study. Postharvest management strategy considering fungicide application is  discussed.
Keywords: Disease progress; Late blight; Phytophthora; Postharvest; Tomato